THE EFFECT OF GOAL ORIENTATION DAN SELF EFFICACY ON ACADEMIC ACHIEVMENT - Bebi Sanusi Sanusi (Pimpinan Cabang Muhammadiyah Kramat Jati, 2020)
Academic achievement is a person's competence related to the realm of knowledge (Algarabel & Daci, 2001) and can be indicated by students' Grade Point Average (GPA) or student performance on their learning tasks (Bryant, 2012). Dweck and Elliot (1983) stated that achievement is an indicator of competence. Poor student academic achievement is a picture of the poor competence of Indonesian education, it is an urgent problem that must be immediately found a solution. The level of academic progress or academic failure is a criterion for the effectiveness of the education system, so research on various variables that effectively affect academic outcomes is urgently needed (Koshnam, Gamari & Gendavani, 2013). From the results of this study, the magnitude of the influence of mastery goal orientation on learning achievement is 4.4% with sig. = 0.001. It can be stated that the influence of mastery goal orientation is significant. The magnitude of the effect of performance goal orientation on learning achievement is 2.3% with sig. = 0.012. This can be stated the significant influence of performance goal orientation. Only these two variables affect student learning outcomes.